Reducing waiting times in geriatric hospitals through lean healthcare tools: a service model - Arias Ura, Felipe (2024)
The purpose of this study is to demonstrate how Lean tools can be used to decrease waiting time for outpatients in a geriatric hospital. The study also evaluates the critical success factors of Lean implementation in the outpatient process. To achieve this, a three-phase service model was proposed, including problem analysis, implementation, and verification. The proposed solution includes the use of Standard Work, Kanban Board, and Poka-Yoke methodologies under the Lean Healthcare approach. The current and improved scenarios were simulated using the Arena software. The study's results showed that the implemented model improved patient satisfaction from 67.50% to 86.17%. This was due to a reduction in waiting time by 47%, total stay time by 44%, and an improvement in the registration process by 13%. This research shows how Lean Healthcare significantly reduces geriatric patient waiting times, which is crucial for this population. This will provide a foundation for this health sector, which has rarely used Lean Healthcare tools, and help administrators and managers in similar situations.